1996
DOI: 10.1046/j.1365-3148.1996.d01-53.x
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia enterocolitica transmission from a red cell unit 34 days old

Abstract: In 1993 the North London Blood Transfusion Centre received its first report of Yersinia enterocolitica transmission from a unit of red cells supplied to a local hospital. The recipient was a 23-year-old male who was neutropenic following a third cycle of chemotherapy for treatment of acute myeloblastic leukaemia (FAB type M6) and received a 34-day-old red cell unit. During transfusion the patient developed septicaemia and endotoxin-mediated shock. The transfusion was stopped immediately and broad spectrum anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 6 publications
0
21
0
1
Order By: Relevance
“…Although storage of RBCC at a low temperature (2 to 8°C) inhibits most bacterial growth, they are still at risk of contamination with psychrophilic bacteria such as Yersinia enterocolitica, which is now the most common cause of transfusionassociated bacterial contamination (5,11,18,22,28). The presence of these bacteria in blood products has often been associated with asymptomatic bacteremia and gastrointestinal illness of the donor (11,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although storage of RBCC at a low temperature (2 to 8°C) inhibits most bacterial growth, they are still at risk of contamination with psychrophilic bacteria such as Yersinia enterocolitica, which is now the most common cause of transfusionassociated bacterial contamination (5,11,18,22,28). The presence of these bacteria in blood products has often been associated with asymptomatic bacteremia and gastrointestinal illness of the donor (11,28).…”
Section: Discussionmentioning
confidence: 99%
“…Platelet concentrate preparations are known to carry a greater risk of bacterial infections, as they are required to be stored at 20 to 24°C (3, 6, 7, 10). With the significantly higher number of red blood cell concentrates (RBCC) transfused, however, the incidence of transfusionassociated bacterial contamination is similar (5,11,18,28). In the French Bacthem case-control study, 41 bacterium-related transfusion reactions were reported during a 2-year period, including 25 following transfusion with RBCC, with 4 fatalities, and 16 following platelet transfusion, with 2 fatalities (23).…”
mentioning
confidence: 99%
“…Techniques such as autologous transfusion that prevent transmission of other blood-borne infections do not prevent this syndrome (Sire et al, 1993;Haditsch et al, 1994). Donor exclusion by screening for recent gastrointestinal symptoms would exclude up to 6% of donors (Grossman et al, 1991) and would impose an unacceptable restriction on the blood supply without excluding risk from asymptomatic donors (McDonald et al, 1996). Reduction in the storage period of whole blood and red cells to less than 25 days would have implications for the blood supply (Hoppe, 1992) and would not eliminate risk.…”
Section: Clinical Manifestations Of Y Enterocolitica Infections (Mikmentioning
confidence: 99%
“…The transmission of Yersinia through pooled platelet concentrates has been reported twice to date [16,18]. It is interesting to note that in several of the reported cases, the transfusion of platelet concentrates passed without incident while RBC concentrates from the same donation caused Yersinia sepsis resulting in death [19][20][21]. No summarised figures over a similar time period exist for Germany.…”
Section: Prevalence and Incidence Of Blood-associated Infections And mentioning
confidence: 99%